Molecular mechanism of anti-inflammatory effects of the proteasome inhibitor MG-132 on Con A-induced acute liver injury in mice. (March 2023) - Shan, Chunlan; Ou, Deyuan; Xiong, Yanling; Cheng, Hongsong; Song, Chun; Li, Mei; Fang, Tian; Cheng, Zhentao; Miao, Fujun
Abstract: MG-132, an aldehyde-based peptide proteasome inhibitor (PI) that binds to the proteasome and reversibly inhibits proteasome activity, has been widely used in experimental research. However, it is not clear whether MG-132 has anti-inflammatory effects on liver injury. The molecular mechanism of the anti-inflammatory effect of the PI MG-132 on Con A-induced acute liver injury (ALI) mice was investigated by ELISA, HE, q RT-PCR, and IHC. The results showed that the serum activities of alanine aminotransferase (ALT) and aspartate aminotransferase (AST) and TNF-α and IL-6 contents of mice in the high and medium dose groups were reduced compared with those in the ALI group. The superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px) levels in liver tissues were significantly increased, and the malondialdehyde (MDA) content was decreased. The pathological sections of mice in the ALI group showed typical ALI manifestations such as significant central venous stasis of liver tissues, cell swelling, and inflammatory cell infiltration. The pathological damage of liver tissues was relieved significantly in the three dose groups, especially in the high-dose group. The transcriptional level of TLR4/NF-κB pathway key factors mRNA was significantly reduced, and the expression of TLR4 and NF-κB P65 protein in liver tissues was significantly and positively correlated with the contents of TNF-α and IL-1β ( p < 0.01). Our findings suggest that MG-132 can alleviate the inflammatory response to Con A-induced ALI and exert a hepatoprotective effect, and its anti-inflammatory effect is related to the inhibition of TLR4/NF-κB signaling pathway activation. Highlights: Different dose of MG-132 showed the anti-oxidative abilities in acute liver injury. MG-132 could have the anti-inflammatory function.